2005
DOI: 10.1046/j.1529-8817.2005.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Loci Contributing to Adult Height and Body Mass Index in African American Families Ascertained for Type 2 Diabetes

Abstract: SummaryHeight and body mass index (BMI) have high heritability in most studies. High BMI and reduced height are well-recognized as important risk factors for a number of cardiovascular diseases. We investigated these phenotypes in African American families originally ascertained for studies of linkage with type 2 diabetes using self-reported height and weight. We conducted a genome wide scan in 221 families containing 580 individuals and 672 relative pairs of African American descent. Estimates of heritability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
0
15
1
Order By: Relevance
“…Hirschhorn et al (2001) identified a height linkage peak on chromosome 3 at 72 cM with a LOD score of 2.3 in a Finnish population. Sale et al (2005) demonstrated linkage of height to chromosome 3 at 84 cM in an African American population with a LOD score of 1.8. Additionally, linkage of spine bone mineral density has been identified on this chromosome in two separate populations at 69 cM (LOD 2.1) and 76 cM (LOD 2.7) (Wilson et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Hirschhorn et al (2001) identified a height linkage peak on chromosome 3 at 72 cM with a LOD score of 2.3 in a Finnish population. Sale et al (2005) demonstrated linkage of height to chromosome 3 at 84 cM in an African American population with a LOD score of 1.8. Additionally, linkage of spine bone mineral density has been identified on this chromosome in two separate populations at 69 cM (LOD 2.1) and 76 cM (LOD 2.7) (Wilson et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Accurate phenotyping of complex traits is paramount in ensuring meaningful results (Schulze and McMahon 2004). In many published studies, height measures were drawn from questionnaires in which height was self reported (Perola et al 2001;Sale et al 2005;Willemsen et al 2004), or the phenotyping method used is not clearly stated (Deng et al 2002;Hirschhorn et al 2001;Wiltshire et al 2002;Xu et al 2002). The reliability of questionnaires has sometimes been verified (Perola et al 2001), but there is no substitute for measures taken by trained observers on calibrated equipment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These fairly low power estimates suggest that additional chromosome regions not detected in the current study might be of great importance for variation in adult height in the studied population. Since the first genome-wide linkage scans for height were performed in 2001 (Hirschhorn et al 2001;Perola et al 2001), several susceptibility loci for height have been reported [for a recent overview see Perola et al (2007)], but, as for most complex phenotypes, only some have been successfully replicated by further studies (Liu et al 2004(Liu et al , 2006Willemsen et al 2004;Sale et al 2005;Shmulewitz et al 2006). The most promising susceptibility loci for height (Score.Max p = 0.005) detected in our current study of sib-pairs from American Samoa was located on chromosome 9q31 at marker D9S1690.…”
Section: Susceptibility Loci For Adult Heightmentioning
confidence: 99%